2010
DOI: 10.1016/j.joca.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of cartilage in recombinant human type II collagen gel in nude mouse model in vivo

Abstract: These results show that rhCII-gel provides good expansion and mechanical support for the formation of cartilage neotissue. RhCII material may allow favorable conditions in the repair of chondral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 48 publications
2
47
0
2
Order By: Relevance
“…Then, the fixed tissues were dehydrated with a series of gradually increasing concentrations of ethanol and embedded in tissue-Tek III embedding paraffin. Histological sections (5 μm in thickness) were cut from the middle part of the tissue and stained with toluidine blue (Serva, Heidelberg, Germany) as described previously (Pulkkinen et al 2010). Immunohistochemical staining was performed with anti-type II collagen mouse monoclonal antibody (Holmdahl et al 1986) and anti-type I collagen rabbit polyclonal antibody (Pulkkinen et al 2010).…”
Section: Histological Stainingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the fixed tissues were dehydrated with a series of gradually increasing concentrations of ethanol and embedded in tissue-Tek III embedding paraffin. Histological sections (5 μm in thickness) were cut from the middle part of the tissue and stained with toluidine blue (Serva, Heidelberg, Germany) as described previously (Pulkkinen et al 2010). Immunohistochemical staining was performed with anti-type II collagen mouse monoclonal antibody (Holmdahl et al 1986) and anti-type I collagen rabbit polyclonal antibody (Pulkkinen et al 2010).…”
Section: Histological Stainingsmentioning
confidence: 99%
“…The extracted PGs were separated in 1.2% agarose gels, as in our previous study (Pulkkinen et al 2010) after a small modification. Briefly, 5 μg extracted PGs was dissolved in 10 μl sample buffer (1% SDS in 1× TRIS/acetic acid/EDTA buffer) and boiled for 5 min in tightly capped, seal-containing plastic tubes.…”
Section: Pg Separation With Agarose Gel Electrophoresismentioning
confidence: 99%
“…In another study, isolated bovine chondrocytes seeded into rhCII gels were injected subcutaneously into the back of nude mouse model. It was observed that this complex offered the ability to promote cell proliferation and mechanical strength for the formation of cartilage [25]. In a recent study, Wang et al used core-shell nanofibrous scaffold fabricated by collagen and poly(L-lactic acid-co-epsilon-caprolactone) to encapsulate rhTGF-β3 and bovine serum albumin into the core of the nanofibers for tracheal cartilage regeneration.…”
Section: Biomaterials In Cartilage Tissue Engineeringmentioning
confidence: 99%
“…22 Cell isolation was performed similarly twice from one animal (once per knee). Viability of the cells was determined before the following investigations.…”
Section: Determination Of Cell Viabilitymentioning
confidence: 99%